A synthesized classification system for best practices - Alwazae, Meshari; Kjellin, Harald; Perjons, Erik (VINE. Very informal newsletter on library automation, 2014)
Purpose – The aim of the study is to propose a classification system for best practices (BPs). The system is intended for organizations that are interested in indexing, storing and retrieving large quantities of BPs. Design/methodology/approach – An extensive literature survey to identify relevant articles by searching e-resource databases, including international journals and conferences related to the use of BP was conducted. A content analysis was conducted on selected articles to identify how BPs can be indexed. Findings – The authors are concerned with identifying what BP frameworks exist in literature and how BPs can be classified based on the features of these BP frameworks. Subsequently, they reviewed the identified frameworks within the literature and built a BP classification system. This classification system consists of a number of features, referred to as variables, where each variable is associated with a set of possible values. Originality/value – The proposed BP classification system is intended to provide a guideline for recognizing general characteristics for all BPs in any domain or organization to aid stakeholders in classifying BPs.